The One Size Does Not Fit All Approach: Case Studies in Modeling Embedded Librarianship. Issue 2 (30th September 2022) - Edford, Rachel L.; Avila, Sandra
Abstract: The pandemic and resulting shift to remote work stressed the importance of distance library services. As librarians explored different modes of engagement, embedded librarianship became increasingly important but also more complicated than before. While there is a wealth of literature on embedded librarianship, few authors agree on how to define it or discuss its specific challenges during the pandemic. This paper will present the experiences of two academic librarians working in different departments at the same institution, informed by the literature; the authors will highlight the complexity of embedded librarianship during this unique time while addressing challenges and offering recommendations.